Rhizomata : A Journal for Ancient Philosophy and Science (De Gruyter, 2013)
Publications in Rhizomata cover the full range of ancient philosophy, with special emphasis on the interaction between philosophy and science. Another thematic priority is the influence of ancient philosophy and its interpretation in the later tradition. Supplementing the articles, discussion notes and reviews, the journal also provides bibliographical documentation of recently published important work in the South-East European region.